A Model for Managing Hidden Curriculum in Banyumas Javanese Language Learning to Instill Cablaka Character in Early Childhood - Imam Satibi; Novan Ardy Wiyani; Hastri Firharmawan; Nurhidayah Nurhidayah (AL-ISHLAH: Jurnal Pendidikan, 2024)
The purpose of conducting this research is to formulate a hidden curriculum management model in Banyumas Javanese language learning to shape the character of cablaka for early childhood. This study uses a qualitative approach to the type of phenomenological research. The data sources in this study were school principals, teachers, and children at Kindergarten Diponegoro 187, Gerduren village. Data was collected using interview, observation, and documentation techniques. The data that has been collected is then analyzed using the data analysis technique of the Miles and Huberman model, which consists of data reduction, data display, and verification stages. The results of the study show that hidden curriculum management in Banyumas Javanese language learning to form cablaka characters for early childhood is designed through three stages. First, agree on the goals to be achieved in learning Javanese Banyumas using the hidden curriculum approach. The aim is to form the cablaka character in early childhood, which is reflected in the Bawor character in the wayang world. Second, folklore and the Ancas tabloid are used as a source of learning in Banyumas Javanese language learning. Third, Banyumas Javanese should be integrated into learning themes and sub-themes, play activities, storytelling activities, and incidental activities. Learning Banyumasan Javanese can contribute to the formation of Cablaka characters in children when they are accustomed to practicing Banyumasan Javanese in their daily lives.